Factors Influencing Maternal Participation in Posyandu Activities in Sangkrah, Surakarta: An Analysis of Socio-Demographic Determinants - Puriastuti, Emma Anastya; Hardiningsih, Hardiningsih; Satia Pratiwi, Dyah Krisnawati; Yunita, Fresthy Astrika (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2025)
Stunting remains a critical public health issue globally, particularly in Indonesia, where efforts to reduce its prevalence are ongoing. Posyandu (Integrated Service Posts) play a pivotal role in monitoring and preventing malnutrition among children. This cross-sectional study aimed to analyze the factors influencing maternal participation in Posyandu activities in the Sangkrah region of Surakarta, an area with unique socio-economic and cultural characteristics. Data were collected from 156 mothers with children under five years old using structured questionnaires and analyzed using SPSS. The findings indicated that younger mothers (